Legal Validity of Blockchain-Based Contracts in Maritime Transport Systems - Riwu, Agustin Leni Magdalen Rohi (Jurnal Ilmu Hukum Kyadiren, 2025)
This study aims to provide a juridical analysis of the application of blockchain technology in maritime transport contracts, with a focus on legal validity, recognition within existing regulatory frameworks, and dispute resolution mechanisms. Employing normative legal research, this study utilizes a statutory and literature review approach to examine the development and legal implications of blockchain technology. The findings indicate that while blockchain enhances transparency and data security, its legal recognition varies across national legal systems. Many countries lack clear regulations to govern blockchain-based contracts, leading to legal uncertainties. Additionally, dispute resolution for such contracts remains largely limited to arbitration mechanisms. This study highlights the need for international regulatory updates to accommodate blockchain technology in maritime transport contracts, ensuring a more standardized and effective legal framework that facilitates broader adoption and legal certainty in global trade.